Headline Salience, Managerial Opportunism, and Over- and Underreactions to Earnings - Huang, Xuan; Nekrasov, Alexander; Teoh, Siew Hong (The Accounting Review, 2018)
ABSTRACT Limited attention theory predicts that higher salience of earnings news implies a stronger immediate market reaction to earnings news and a weaker post-earnings announcement drift (PEAD) or reversal (PEAR). Using a new measure, SALIENCE, defined as the number of quantitative items in an earnings press release headline, we find strong evidence consistent with salience effects. Higher SALIENCE is associated with stronger announcement reaction and subsequent PEAR. Managers are more likely to choose higher SALIENCE before selling shares in the post-announcement period and when earnings are high, but less persistent, and to choose lower SALIENCE before stock option grants. The results are robust to using residual salience and an extended set of control variables. The findings are consistent with managers opportunistically headlining positive financial information in the earnings press release to incite over-optimism in investors with limited attention.